Pelaksanaan Layanan Bimbingan dan Konseling dalam Membantu Siswa Menemukan Identitas Diri di SMAN 6 Kepahiang - Triani Eka Pitri (Universitas PGRI SUMATERA BARAT, 2023)
Self identity is awareness and continuity in knowing oneself, accepting personality, roles, commitments, orientations, life goals in the individual so that they are able to behave according to their own needs and also in society. Self-identity can be found if a student has successfully passed a crisis of self-identity and has been able to adjust the handling in dealing with a crisis of self identity. The self-identity of students at Kepahing 6 Public High School is still experiencing an identity crisis due to a lack of students' understanding of self-identity but for the implementation of Guidance and Counseling services in helping students find self-identity has been provided by the Guidance and Counseling teacher. This is what makes it gradually able to pass through the student's identity crisis. With this researcher wants to deepen research regarding the implementation of Guidance and Counseling in helping students find self identity. The method in this study uses a qualitative approach. As for the subjects of this study were students who had not found their identity, Guidance and Counseling teachers, homeroom teachers and student representatives. The subject approach of this study used purposive sampling. Data collection techniques through observation, interviews and documentation. The results showed that the self identity of the students of Kepahiang 6 Public High School who had been given Guidance and Counseling in helping students find their own identity was gradually able to pass through the identity crisis as students who could know themselves, were able to accept themselves and their environment, were able to adapt. As for the implementation of Guidance and Counseling at Kepahiang 6 State Senior High School in accordance with the planning of the Guidance and Counseling program and the implementation of Guidance and Counseling teacher providing direct services, the guidance media provided are posters placed in the Guidance and Counseling room and in schools and Guidance and Counseling teachers Counseling also conducts home visits after carrying out evaluations and follow-up on the implementation of Guidance and Counseling services in accordance with the Guidance and Counseling POP of 2016, as for the Guidance and Counseling teachers' efforts to help students find self-identity by providing information services, group guidance services and individual counseling. Keywords: identity crisis, students, guidance and counseling